Sociology of Literature in a Collection of Kang Maksum's Short Stories by A. Mustofa Bisri - Anjani, Ni Pande Nyoman Dri; Supriyono, Supriyono; Sutiyono, Akhmad; Windriani, Dian (IJLHE: International Journal of Language, Humanities, and Education, 2020)
The purpose of this study is to identify and describe the sociology of literature in the collection of short stories Kang Maksum, in terms of content, theme, and purpose. The subject of this research is a collection of short stories Kang Maksum by A. Mustofa Bisri. This study uses descriptive and qualitative research method. This study collects data qualitatively, such as by interpretation, analysis, and evaluation. The results of the study shows that the content of the short story Kang Maksum by A. Mustofa Bisri in terms of the sociology of literature describes the social life that is actually experienced by the writer himself, namely A. Mustofa Bisri. Through the short stories, A. Mustofa Bisri wants to convey messages that readers should uphold the simplicity in life as their principle. Therefore, the social themes raised by Mustofa Bisri in his short stories become valuable lesson for readers as well as a depiction of the social life in certain community.